The Effect of Temperature and Time on Quality of Banana Peel Flour - Kusmayanti, Eva; Zalfa, Sarah Haura; Aktawan, Agus (Universitas Ahmad Dahlan, 2020)
Banana peel waste is usually only used as animal feed and as raw material for bioethanol manufacture. Banana peels have a large nutritional content. Banana peels can be used as an ingredient in flour. Local-based alternative food sources are a priority. Among the various types of functional food, flour substituents such as banana peel flour is an interesting topic because of the people need for it wheat flour is an inevitable necessity. The aim of this study conducted direct studies of the physical characteristics of cooking banana peel flour as well as studying how the effect of temperature and time on the quality of cooking banana peel flour. Methode this research is direct research with the type of data used is primary data namely data obtained from research results. The results of the study generally show that the characteristics of banana peel flour are powdery, normal smell (typical of bananas), has a slightly bitter taste, and brown. The conclusion of this study is the banana skin suitable as a flor substituent with relatively good characteristics when used as a substitute for wheat flour.